Milestones in Natural Lubrication of Synovial Joints - Ruggiero, Alessandro (Frontiers in Mechanical Engineering, 2020)
For years, the physical and mathematical modeling of tribological phenomena in natural human synovial joints has been a great challenge for researchers and scientists. This short review aims to summarize the main findings on lubrication modeling of human synovial joints over the years, starting from first insights and then underlining the evolution of the proposed theories. The complexity of natural human synovial joints, in which biological, fluid dynamic, and tribological phenomena takes place, makes this research area fascinating for scientists from several investigation fields. This manuscript underlines the necessity of deep scientific cooperation between researchers from different branches of the involved disciplines to achieve complete knowledge of these tribo-systems by taking in to account different points of view.